Pemikiran Ibrahim Hosen Tentang Konsep Pernikahan dan Kontribusinya Terhadap Pembaruan Hukum Perkawinan di Indonesia - Sari, Widya; Arif, Muhammad; Elkhairati, Elkhairati (AL-ISTINBATH : Jurnal Hukum Islam, 2021)
This paper aims to examine Ibrahim Hosen's thoughts on the meaning and purpose of marriage and his contribution to the reform of marriage law in Indonesia. How Ibrahim Hosen's thinking about marriage is limited to the definition and purpose of marriage, how various thoughts exist and how the contribution of Ibrahim Hosen's thoughts to reforming marriage law in Indonesia is the problem of this research. This is a library research. The data analysis method used is content analysis. As a result, the definition of ownership in the marriage contract according to Ibrahim Hosen is not a contract to have a wife's body, making a wife an object by the husband. However, the right of ownership in the definition of marriage means the right to have the use of the husband against the wife, in addition to the haram husband who feels the pleasure of the wife. Based on this, it can be concluded that there is no patriarchal element in the definition of marriage as explained by the fiqh scholars. Ibrahim Hosen explained that marriage in Islam aims to build a prosperous household full of sakinah, mawaddah, and mercy. Therefore, linking the husband's obligation to provide for his wife with tamkin is clearly not right, because it seems as if the purpose of marriage is just a matter of sex. This thinking must be corrected by conducting a review, because the obligation to provide a living takes effect after the marriage contract occurs. Therefore, the provisions of Article 80 paragraph [5] KHI related to the relationship between husband and wife and tamkin, need to be revised.